Microorganisms for Green Revolution Volume 2 : Microbes for Sustainable Agro-ecosystem (Microorganisms for Sustainability,, 2018)
This book explores basic and applied aspects of microorganisms, which have a unique ability to cope with abiotic stresses such as drought, salinity and changing climate, as well as biodegrader microorganisms and their functional roles. Further, readers will find detailed information on all aspects that are required to make a microbe "agriculturally beneficial." The book's primary focus is on microbes that are essentially "hidden miniature packages of nature" that influence agro-ecosystems. Inviting papers by prominent national and international scientists working in the field of agricultural microbiology, it addresses the biogdegrader group of microbial inoculants. Each chapter covers the respective mechanism of action and recent advances in agricultural microbiology. In addition, the book especially highlights innovations involving agriculturally beneficial microorganisms, including strategies for coping with a changing climate, and methods for developing microbial inoculants and promoting climate-smart agriculture. The information presented here is based on the authors' extensive experience in the subject area, gathered in the course of their careers in the field of agricultural microbiology. The book offers a valuable resource for all readers who are actively involved in research on agriculturally beneficial microorganisms. In addition, it will help prepare readers for the future challenges that climate change will pose for agriculture and will help to bridge the current gaps between different scientific communities.